Physical science for senior high school - Borra-Cudera, Rizalyn; Carreon, Hazel Gumanay; Morales, Normeliza Escoton (Malabon City : Mutya Publishing House, Inc., 2016)
"Interconnectedness of various topics from the fields of chemistry, physics and astronomy is highly evident in the Physical Science course. This book is presented briefly and concisely for students to easily follow the discussions of the topics. It also highlights the evolution of our understanding of matter, motion, electricity, magnetism, light and the universe form ancient times to the present. Students will know more about the contributions of Greek philosophers in understanding the universe as well as the eminent scientists in Physics and Chemistry. But what makes the course more interesting is the inclusion of the applications of physics and chemistry concepts in the contexts of atmospheric phenomena, cosmology, astronomy, vision, medical instrumentation, space technology, drug, sources of energy, pollution and recycling, fitness and health and cosmetics. So through this, students will highly appreciate the course and will surely relate the course with what is happening in their daily lives."
Includes references.
English text.
Keywords: Physical sciences